Incostitucionalidad de la prisión preventiva y la vulneración a la tutela judicial efectiva, la seguridad jurídica y el debido proceso - Andrade Diaz, Marjorie Alexandra (2018)
In the present research work, the analysis of case No.16789-2017-00123 of criminal matters is developed, and it is a matter of considering whether the judgment in which the judgment was rendered in favor of the prosecution is legitimate. followed against Mr. Jorge Espinoza Guerrero, former Vice President of the Republic of Ecuador, for the alleged crime of Illicit Association. To be able to consider the unconstitutionality of the change of precautionary measures issued in a judgment, which changes the prohibition of leaving the country to preventive detention, prohibition of the alienation of assets and retention of accounts, although for the change of said measures there should be distrust that the alleged accused is going to leave the country, something that could not be verified with total clarity, is what leads to the realization of this investigative work. Through the correct application of techniques and methods, our work has been able to focus on the object of study, which will be developed on preventive detention and the violation of effective judicial protection, legal security and due process. The methodology used in it was based mainly on the descriptive method, since it establishes an analysis of characteristics, parameters, situations and thus describe each of the parties as precautionary measures in proceedings in which the deprivation of freedom. The main objective of this investigation is to determine whether within the substitution of precautionary measures prohibiting the country from going to preventive detention in the process No.16789-2017-00123 that is still against the Mr. Jorge Espinoza Guerrero, former vice president of the Republic of Ecuador, is constitutional and legal, since no convincing legal support was found, nor threat that is necessary for these measures to be changed, rather it became known the bad performance of the judge so the defendant was not given the constitutional guarantees and therefore the due process was violated and violated. The constitution of the republic of Ecuador as the supreme legal norm or rector, has as its purpose the fulfillment of its principles, one of its fundamental duties as a state is to respect and enforce the rights that are fully guaranteed in the constitution by all and each of its constituents, which is typified in the aforementioned rule in Article 11, paragraph 9, therefore the violation of due process must be sanctioned by those who knowingly omit certain formalities and making the right bad practice, in which the rights of the defendant remain totally defenseless, although there are principles for due process and right to defense, these in the case analyzed are in total inequality.